- Anastomoses choledochoduodenal gallstones - Huguier, Michel; Houry, S. Houry; Pascal, G. (Cirugía del Uruguay, 1986)
After choledochotomy different procedures can be utilized. In biliary lithiasis, the authors frequently perform a choledochoduodenal anastomosis in aged patient. This paper deals with the study of results of choledochoduodenal anastomosis in a series of 77 patients operated on consecutively.